Features of cell death, mitochondrial activation and caspase dependence of rabbit anti-T-lymphocyte globulin signaling in lymphoblastic Jurkat cells are distinct from classical apoptosis signaling of CD95 - Ziegler, Christian Martin; Finke, Jürgen; Grüllich, Carsten (Leukemia and lymphoma, 2016)
Rabbit anti-T-lymphocyte-globulin (ATG) is used for immunosuppression in organ and stem cell transplantation. The aim of this study was to investigate ATG-induced cell death compared to CD95-signaling of apoptosis. We measured features of cell death at the cell membrane, mitochondria, nuclei and caspase-3 cleavage. We used the following inhibitors: the caspase inhibitor N-benzyloxycarbonyl-Val-Ala-Asp (O-Me)-fluoromethyl ketone (zVAD-fmk), the serine protease inhibitors 3,4 dichloroisocoumarin (DCI) and N-alpha-tosyl-L-lysinyl-chloromethylketone (TLCK) and the reducing agent N-acetycysteine (NAC). ATG-induced cellular changes were rapid, included mitochondrial membrane permeability (MMP) induction and annexin V/propidium iodide (PI) positivity but little caspase-3 activation and nuclear morphology changes. MMP was not sensitive to caspase inhibition, serine protease inhibition with DCI moderately reduced MMP. These findings were in contrast to CD95-signaling. Interestingly, TLCK massively augmented CD95-induced MMP which could be abrogated by NAC. In conclusion, ATG-signaling differs in features and kinetics from CD95-induced apoptosis with caspase-independent mechanisms involved in MMP.